Molecularly Imprinted Polymer-Coated CdTe Quantum Dots for Fluorometric Detection of Sulfonamide Antibiotics in Food Samples - Mortari, Bianca [UNESP] (2023)
This work reports the development and application of a highly selective core@shell-based quantum dot–molecularly imprinted polymer (QD@MIP) sensor for the detection of sulfadiazine (SDZ)—an antibiotic which belongs to the sulfonamide family. The synthesis of the smart material or MIP (molecularly imprinted polymer) was carried out by a precipitation method directly on the quantum dot surface, which played the role of a fluorescent probe in the optical sensor. The synthesized polymer was characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. Fluorescence experiments were performed in order to evaluate the effects of pH, interaction time of the QD@MIP with the analyte and SDZ concentration in different matrices. Under optimized conditions, a linear concentration range of 10.0–60.0 ppm and a limit of detection of 3.33 ppm were obtained. The repeatability and reproducibility of the proposed QD@MIP were evaluated in terms of the RSD, where RSD values of less than 5% were obtained in both tests. Selectivity studies were carried out in the presence of four possible interfering substances with quenching properties, and the signals obtained for these interferents confirmed the excellent selectivity of the proposed sensor; the imprinting factor value obtained for SDZ was 1.64. Finally, the proposed sensor was applied in real animal-based food samples using a spiked concentration of SDZ, where the recovery values obtained were above 90% (experiments were performed in triplicate).